ANALISIS PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN DESA WISATA PRINGGASELA KECAMATAN PRINGGASELA KABUPATEN LOMBOK TIMUR - Khairun Nisa; Suharti Suharti (Yayasan Nusantara Hasana Berdikari, 2023)
This research was motivated by the lack of local youth’s attention and motivation in developing the Pringgasela tourism village, who are the generation that will continue the aspirations and hopes of their parents to maintain and develop the village’s potential for the welfare and prosperity of its people. This research aimed to describe and analyze the types and levels of society’s participation in developing Pringgasela Tourism Village, East Lombok. The design of this research was qualitative and data collection techniques were obtained through observation, interviews, and documentation. The data analysis in this research used Miles and Huberman's theory which consisted of three steps, namely data reduction, data presentation, and drawing conclusions. The results of this research indicated that society’s participation in the development of Pringgasela Tourism Village, East Lombok was in the form of authentic participation, namely participation in the form of contributions to the program, involvement in decision making, and receiving program benefits. Meanwhile, the level of society’s participation fell into the category of citizen power and tokenism.